Hydrogels Based on Poly(aspartic acid): Synthesis and Applications - Adelnia, Hossein; Blakey, Idriss; Little, Peter J.; Ta, Hang T. (Frontiers in Chemistry, 2019)
This review presents an overview on the recent progress in the synthesis, crosslinking, interpenetrating networks and applications of poly(aspartic acid) (PASP)-based hydrogels. PASP is a synthetic acidic polypeptide that has drawn a great deal of attention in diverse applications due particularly to its biocompatibility and biodegradability. Facile modification of its precursor, poly(succinimide) (PSI), by primary amines has opened a wide window for the design of state-of-the-art hydrogels. Apart from pH-sensitivity, PASP hydrogels can be modified with suitable species in order to respond to the other desired stimuli such as temperature and reducing/oxidizing media as well. Strategies for fabrication of nanostructured PASP-based hydrogels in the form of particle and fiber are also discussed. Different cross-linking agents for PSI/PASP such as diamines, dopamine, cysteamine, and aminosilanes are also introduced. Finally, applications of PASP-based hydrogels in diverse areas particularly in biomedical are reviewed.